New data on morphology and natural history of Deltamys kempi Thomas, 1919 (Cricetidae, Sigmodontinae) from central-eastern Argentina - Teta, Pablo; Cueto, Gerardo; Suárez, Olga (Zootaxa, 2007)
We provided new data on morphology and natural history of the rare sigmodontine rodent Deltamys kempi. Field work was conducted in Reserva Costanera Sur, Buenos Aires, central-eastern Argentina during two consecutive years. The glans penis of D. kempi is short and stocky and sub-cylindrical in appearance; the stomach is unilocular-hemiglandular; the baculum has a well developed cartilaginous portion, with two lateral digits and a central one; gall bladder is present. We also describe for the first time the soft palate and the manus and pes morphology. Soft palate, stomach, glans penis, manus and pes morphology of Deltamys is similar to Akodon, its hypothesized sister taxon. D. kempi was more frequently captured in relatively pure stands of the tall grass Cortaderia selloana. According to the available records in Argentina, D. kempi occupies preferably grassy marshes and dense gramineous patches in gallery forest. Reproductive season seems to start at the late winter-early spring and to last until the end of summer-early autumn. Stomach contents of four individuals had mainly insects and insect larvae. Ectoparasites found in D. kempi included the Acari Androlaelaps fahrenholzi, A. aff. A. rotundus and Laelaps paulistanensis, and the Siphonaptera Polygenis sp.